2014
DOI: 10.4274/haseki.1079
|View full text |Cite
|
Sign up to set email alerts
|

İkinci Basamak Bir Devlet Hastanesinin KBB Kliniğindeki Tonsillektomi Sonrası Kanama Hastalarının Özellikleri ve Bu Hastalara Yaklaşımlarımız

Abstract: Özet Amaç: İkinci basamak bir devlet hastanesinde yapmış olduğumuz tonsillektomi operasyonları sonrası kanayan hastaların özelliklerini ve bu hastalara yaklaşımlarımızı araştırdık. Yöntemler: Bu geriye dönük çalışmada Mart 2009-Aralık 2012 tarihleri arasında ikinci basamak devlet hastanesi kulak burun boğaz (KBB) kliniğinde (Babaeski Devlet Hastanesi) yapılmış toplam 322 tonsillektomi vakasından postoperatif kanaması olan 11'i kadın yedisi erkek, ortalama yaşı 19,8 (5-45 yaş) olan toplam 18 hasta (%5.5) sunuld… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
0
2
0
1
Order By: Relevance
“…Wei et al [6] found that 89 of 90 bleeds were secondary in 4,662 patients. The causes of secondary bleeding are residual tonsillar tissue, infection, an incorrect diet such as an acidic liquid or solid food, trauma, and the use of nonsteroidal anti-inflammatory drugs [7,8]. However, we attribute the bleeding in our patients to extremely hot environments.…”
Section: Summermentioning
confidence: 64%
See 1 more Smart Citation
“…Wei et al [6] found that 89 of 90 bleeds were secondary in 4,662 patients. The causes of secondary bleeding are residual tonsillar tissue, infection, an incorrect diet such as an acidic liquid or solid food, trauma, and the use of nonsteroidal anti-inflammatory drugs [7,8]. However, we attribute the bleeding in our patients to extremely hot environments.…”
Section: Summermentioning
confidence: 64%
“…If conservative methods are insufficient, surgical intervention is required, and may include suturing, electrocauterization, and/or ligation of the external carotid artery branches. Elbistanli et al [7] reported that 77.7% of cases required surgical intervention; the figures of Wei, Sayin et al [6,12] were 47% and 28%, respectively. We used chemical cauterization (a silver nitrate bar) only; no surgical interventions were required.…”
Section: Summermentioning
confidence: 99%
“…Literatürde sekonder kanama nedenlerini açıklayan yayınlar incelendiğinde asitli sıvı gıda (bira ve kola) alımı sonrası kanama Elbistanlı ve ark. 16 yaptığı çalışmada bildirilmiştir. Sayın ve ark.…”
Section: Discussionunclassified